Xinmailong injection on left ventricular remodeling and inflammatory mediators in patients with CHF: a systematic review and meta-analysis - Han, Xu; Chen, Xi; Liu, Yanling; Yang, Jie; Nie, Wuzhi; Yang, Mingjiu; Mou, Xinglang (Frontiers in Pharmacology, 2024)
Background: Chronic heart failure (CHF) is a prevalent and highly challenging cardiovascular disease associated with high mortality rates. The occurrence and progression of CHF are closely linked to left ventricular remodeling (LVR) and inflammation. Addressing LVR and reducing inflammation can significantly slow down the progression of CHF and improve patient prognosis.Objective: To evaluate the effects of Xinmailong injection (XMLI) on LVR and inflammatory mediators in CHF patients.The randomized controlled trials investigating the effectiveness of XMLI treatment for CHF were retrieved from 8 databases up until December 31, 2023. To evaluate the methodological quality of included studies, the Cochrane bias risk tool was employed. Furthermore, statistical analysis, sensitivity analysis, and publication bias assessment were conducted using Stata 17.0 software.Compared with conventional treatment (CT), the combination therapy of XMLI and CT significantly improved LVR and reduced inflammatory mediators, mainly manifested by an increase